A kind of agglomerated particles and preparation method thereof, and resin composition containing the same

By using water-soluble cationic polymers containing nitrogen functional groups as a coagulant, the problem of high metal ion residues in latex coagulant materials is solved, the oxidation induction period is extended and the antibacterial and anti-mold performance is improved, and the overall performance of the resin composition is improved.

CN118978619BActive Publication Date: 2025-03-25LIAONING KINGFA SCI & TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411456034.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-03-25
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The existing latex coagulation materials have high metal ion residues during the coagulation process, resulting in a decrease in the oxidation-induced period and an increase in the ash content of the product, and insufficient impact resistance and antibacterial and mildew resistance.

Method used

Water-soluble cationic polymers with nitrogen-containing functional groups are used as a coagulant to kill bacteria and fungi through electrostatic interactions, reduce the residual amount of metal ions, prolong the oxidation induction period, and improve the antibacterial and anti-mold effect.

Benefits of technology

The metal ion residue is reduced, the oxidation induction period is extended, and the yellowing index is reduced, while the impact resistance and antibacterial and mildew resistance of the resin composition are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention provides a condensed particle and a preparation method thereof, and a resin composition containing the condensed particle. The condensed particle includes a vinyl polymer and a coagulant; the coagulant includes a water-soluble cationic polymer having a nitrogen-containing functional group; the number average molecular weight of the water-soluble cationic polymer is ≤16000 g / mol. In the present invention, the coagulant uses a water-soluble cationic polymer having a specific number average molecular weight and a nitrogen-containing functional group, so that the obtained condensed particles have low metal residue, long oxidation induction period, low yellowing index and antibacterial and mildew-proof effect; so that the resin composition including the condensed particles also has good heat-oxidative aging resistance and antibacterial and mildew-proof performance; at the same time, the condensed particles can also be used as an impact modifier to improve the impact resistance of the resin composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of latex coagulation materials, and in particular relates to coagulation particles and a preparation method thereof, and a resin composition containing the coagulation particles. Background Art

[0002] Aromatic vinyl graft copolymers, such as butadiene-styrene-acrylonitrile copolymer (ABS), butadiene-methyl methacrylate-styrene-acrylonitrile copolymer (MABS), butadiene-methyl methacrylate-styrene copolymer (MBS), acrylonitrile-styrene-acrylate monomer copolymer (ASA), etc., can be synthesized by a variety of methods, such as bulk polymerization, suspension polymerization, solution polymerization and emulsion polymerization. Compared with other polymerization methods, monomers can more easily obtain latex with large molecular weight, specific particle size or graft structure through emulsion polymerization. When a solid product is required, the polymer in the latex needs to be separated through a coagulation process. The mechanism of this process is to use chemical or physical methods to destroy the stability of the latex, so that the particles in the latex are aggregated, thereby separating the polymer from the latex to form latex coagulated particles. This latex coagulated particle with a specific particle size and a low glass transition temperature can be used as a good toughening agent to provide the material with good impact resistance.

[0003] At present, the most mature technical solution in industrial production is to mix latex with acid or its metal salt under heating conditions, and to aggregate and coagulate the colloid particles by destroying the double electric layer of latex. It includes the following steps: 1. Prepare a coagulant solution containing acid and metal salt; 2. Mix the coagulant solution with polymer latex under heating and stirring conditions to form a coagulation slurry; 3. Add an appropriate amount of sodium hydroxide solution to adjust the pH of the slurry to near neutral; 4. Separate the slurry from solid to liquid; 5. Wash and dry the rubber powder to obtain latex coagulation particles. Among them, the acid can be one of organic acids or inorganic acids, including: sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, acetic acid, citric acid, etc.; the metal salt can be one of magnesium sulfate, aluminum sulfate, calcium chloride, aluminum chloride, ferric chloride, etc.; especially for ABS materials, when only acid coagulation is used, the colloid particles in the latex cannot be completely coagulated, that is, when the coagulation slurry is separated from solid and liquid by equipment such as a centrifugal dehydrator, the liquid phase is a turbid liquid. A certain amount of inorganic salt must be added to promote the complete coagulation of latex during the coagulation process. However, some metal ions in inorganic salts will remain in the rubber powder, which will reduce the oxidation induction period (OIT) of the agglomerated particles and increase the ash content of the product. Therefore, a large amount of desalted water is generally required for washing. The washing water containing a large amount of metal ions poses a challenge to sewage treatment, which is not conducive to reducing production costs or protecting the environment, such as the solutions disclosed in patents such as US33285073A, US24820562A, US61229745A, and US06515663.

[0004] In addition, resin products such as ABS play an indispensable role in people's daily life and industry and agriculture, but the existing resin products have poor impact resistance, and long-term use and accumulation will cause a large number of bacteria to grow, threatening food safety and human health. In order to solve its antibacterial properties, antibacterial agents are often added to plastics to form antibacterial resins and resin products. At present, the mainstream antibacterial materials of antibacterial resins on the market are silver ion antibacterial agents and ZnO series antibacterial agents, but these antibacterial agents may have an adverse effect on the thermal oxidation aging performance of the resin, and when added to the resin products, they need to be made into antibacterial masterbatch first to ensure that the antibacterial agent has a uniform dispersion effect in the resin, which is complex and costly.

[0005] Therefore, it is an urgent problem to be solved in the art to develop a condensed particle with less metal salt residue, good heat and oxygen aging resistance, and the ability to improve the impact resistance and antibacterial and mildew resistance of resin materials. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention aims to provide a condensed particle and a preparation method thereof, and a resin composition containing the condensed particle. The condensed particle has a low metal ion residue, a long oxidation induction period, a low yellowing index, and antibacterial and mildew-proof effects; when used to prepare a resin composition, it can not only improve the heat-oxidative aging resistance of the resin composition, but also improve the impact resistance and antibacterial and mildew-proof effects of the resin composition.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a condensed particle, wherein the condensed particle comprises a vinyl polymer and a coagulant; the coagulant comprises a water-soluble cationic polymer having a nitrogen-containing functional group; and the number average molecular weight of the water-soluble cationic polymer is ≤16000 g / mol.

[0009] In the present invention, the coagulant is a water-soluble cationic polymer having nitrogen-containing functional groups, and the number average molecular weight of the water-soluble cationic polymer is ≤16000 g / mol, and the obtained coagulated particles have low metal residue, long oxidation induction period and low yellowing index; and the water-soluble cationic polymer having nitrogen-containing functional groups has a high surface charge and can kill bacteria and fungi through electrostatic interaction, and has good antibacterial and mildew-proof effects; thereby, the resin composition including the coagulated particles also has excellent heat-oxidative aging resistance and good antibacterial and mildew-proof effects, and the coagulated particles can also improve the impact resistance of the resin composition.

[0010] In the present invention, the number average molecular weight of the water-soluble cationic polymer is ≤16000 g / mol, for example, it can be 500 g / mol, 1000 g / mol, 1500 g / mol, 2000 g / mol, 2500 g / mol, 3000 g / mol, 3200 g / mol, 3500 g / mol, 3800 g / mol, 4000 g / mol, 4200 g / mol, 4500 g / mol, 4800 g / mol, 5000 g / mol, 5200 g / mol, 5500 g / mol, 5800 g / mol, 6000 g / mol, 6200 g / mol, 6500 g / mol, 6800 g / mol, 7000 g / mol, 7500 g / mol, 8000 g / mol, 8500 g / mol, 9000 g / mol, 9500 g / mol, 10000 g / mol g / mol, 11000 g / mol, 12000 g / mol, 14000 g / mol, 16000 g / mol, and ranges of any two thereof.

[0011] Preferably, the number average molecular weight of the water-soluble cationic polymer is 500-15000 g / mol, preferably 1500-10000 g / mol, and more preferably 2500-6600 g / mol.

[0012] In the present invention, if the number average molecular weight of the water-soluble cationic polymer is too small, the water-soluble cationic polymer will be lost too much during solid-liquid separation, and the antibacterial performance of the agglomerated particles will be poor; if the number average molecular weight is too high, the solubility of some water-soluble cationic polymers will be low, resulting in a high content of residual coagulant in the agglomerated particles, making it difficult to remove metal ions during the washing process, and the cytotoxicity of the obtained agglomerated particles will be relatively large, and the resin composition prepared thereby may cause skin irritation.

[0013] Preferably, at 25° C. and a pH value of 5 to 9, the surface potential of the water-soluble cationic polymer is 8 to 82 mV, for example, 8 mV, 10 mV, 12 mV, 14 mV, 15 mV, 16 mV, 18 mV, 20 mV, 22 mV, 24 mV, 26 mV, 28 mV, 30 mV, 32 mV, 34 mV, 36 mV, 38 mV, 40 mV, 42 mV, 44 mV, 46 mV, 48 mV, 50 mV, 52 mV, 54 mV, 56 mV, 58 mV, 60 mV, 62 mV, 64 mV, 66 mV, 68 mV, 70 mV, 72 mV, 74 mV, 76 mV, 78 mV, 80 mV, 82 mV, or any two thereof; preferably, 15 to 75 mV, more preferably 28 to 50 mV.

[0014] In the present invention, the surface potential of the water-soluble cationic polymer is too small, the surface charge is insufficient, and the latex is difficult to completely demulsify; the surface charge of the water-soluble cationic polymer is too high, and the cytotoxicity is relatively large, resulting in certain skin irritation to the agglomerated particles and resin compositions prepared from such water-soluble cationic polymers.

[0015] Preferably, at room temperature, the solubility of the water-soluble cationic polymer is ≥10 g / L, for example, it can be 10 g / L, 12 g / L, 14 g / L, 16 g / L, 17 g / L, 18 g / L, 19 g / L, 20 g / L, 22 g / L, 24 g / L, 26 g / L, 28 g / L, 30 g / L, 32 g / L, 34 g / L, 36 g / L, 38 g / L, 40 g / L, 42 g / L, 44 g / L, 46 g / L, 48 g / L, 50 g / L, 55 g / L, 60 g / L, 70 g / L, 100 g / L, 200 g / L, 300 g / L, 400 g / L, 500 g / L, 600 g / L, 800 g / L, 1000 g / L, 1200 g / L g / L, 1400 g / L, 1500 g / L; further preferably, the solubility is ≥100 g / L, and more preferably, the solubility is ≥1000 g / L.

[0016] Preferably, the nitrogen-containing functional group includes at least one of an amide group, an amine group, an ammonium group, a guanidine group or a nitrogen-containing aromatic group, preferably at least one of an amine group, an ammonium group or a guanidine group.

[0017] Preferably, the water-soluble cationic polymer includes at least one of chitosan, polyamino acids and derivatives thereof, polyhexamethylene biguanide and salts thereof, acrylic acid ester polymers containing quaternary ammonium groups, or polycarbonate polymers containing quaternary ammonium groups.

[0018] Preferably, the polyamino acid and its derivatives include at least one of polyamino acid, quaternized derivatives of polyamino acid, guanylated derivatives of polyamino acid or quaternized and guanylated derivatives of polyamino acid.

[0019] In the present invention, the "and" in the "polyamino acids and their derivatives, polyhexamethylene biguanide and their salts" refers to and / or relationships, for example, polyamino acids and their derivatives include polyamino acids and / or polyamino acid derivatives. If the same expressions are used below, they represent the same meanings.

[0020] In the present invention, the polyamino acids and their derivatives include linear polyamino acids and their derivatives and / or branched polyamino acids and their derivatives.

[0021] In the present invention, the polyamino acids and their derivatives include homopolymeric polyamino acids and their derivatives and / or copolymeric polyamino acids and their derivatives.

[0022] In the present invention, the monomers of the polyamino acid include, but are not limited to, any one or at least two of lysine, arginine, alanine, isoleucine, phenylalanine, tryptophan, histidine, and glutamine.

[0023] In the present invention, the water-soluble cationic polymer can be purchased from the market or prepared by conventional methods.

[0024] Exemplarily, the preparation method of linear homopolymeric amino acid or linear copolymeric amino acid can adopt N-carboxyl cyclic anhydride (NCA) ring-opening polymerization method; specifically, the method comprises: mixing NCA-amino acid monomer with solvent to obtain an amino acid solution with a concentration of 0.1-0.4 g / mL; mixing an amine compound with solvent to obtain an amine compound solution with a concentration of 2-20 mg / mL; mixing the amino acid solution and the amine compound solution, and stirring at room temperature for 24-96 h; sedimenting and drying the obtained reaction mixture to obtain product A; then mixing product A with trifluoroacetic acid to obtain a trifluoroacetic acid solution of product A with a concentration of 0.1 g / mL, adding 0.2-0.6 times the volume of trifluoroacetic acid hydrogen bromide acetic acid solution (mass fraction of hydrogen bromide is 20-40 wt%) thereto, and reacting at room temperature for 1-5 h later, after settling and drying, the dried solid is redissolved in water, the pH value is adjusted to 8-10 with an alkaline compound, and the linear homopolymer amino acid or linear copolymer amino acid is obtained by settling and drying again. The amine compound includes but is not limited to propylamine; the solvent includes but is not limited to N,N-dimethylformamide (DMF); the difference between the preparation methods of the linear homopolymer amino acid and the linear copolymer amino acid is only the different monomer raw materials; when preparing the linear homopolymer amino acid, the monomer is a single amino acid monomer; when preparing the linear copolymer amino acid, the monomers are equimolar amounts of different amino acid monomers.

[0025] Exemplarily, the preparation method of the branched homopolymeric amino acid and the branched copolymeric amino acid can be as follows:

[0026] An amino acid monomer or its hydrochloride is mixed with an aqueous solution of an alkaline compound in a mass ratio of (2-5):1, and reacted at 200-300°C for 20-50 min in the presence of a protective atmosphere. The obtained product is precipitated and dried to obtain the branched homo-amino acid or branched copolymer amino acid; the aqueous solution of the alkaline compound includes but is not limited to an aqueous potassium hydroxide solution; the mass fraction of the aqueous potassium hydroxide solution is 10-30 wt%; the preparation methods of the branched homo-amino acid and the branched copolymer amino acid differ only in the different monomer raw materials; when preparing the branched homo-amino acid, the monomer is an amino acid monomer; when preparing the branched copolymer amino acid, the monomers are equimolar amounts of different amino acid monomers.

[0027] Exemplarily, the preparation method of the quaternary ammonium derivative of the polyamino acid includes: mixing the polyamino acid with a quaternary ammonium agent and a solvent to obtain a reaction solution; wherein the mass ratio of the polyamino acid to the quaternary ammonium agent in the reaction solution is (1-4):1, and the total concentration of the polyamino acid and the quaternary ammonium agent in the reaction solution is 0.02-0.1 g / mL; reacting the reaction solution at 30-60°C for 12-36 hours, settling, and drying to obtain the quaternary ammonium derivative of the polyamino acid; the polyamino acid includes a linear homopolymer polyamino acid, a linear copolymer polyamino acid, a branched homopolymer polyamino acid, or a branched copolymer polyamino acid; the quaternary ammonium agent includes a compound containing an acrylamide group and / or an ammonium group, such as an N,N-dimethyl-N-alkyl acrylamide compound, wherein the alkyl group can be a straight chain or branched alkyl group of C7-C18; or, a (2-acrylamideethyl) ammonium salt having different substituents on N, wherein the substituents include a straight chain or branched alkyl group of C1-C10.

[0028] Exemplarily, the method for preparing the guanidinium derivative of the polyamino acid comprises the following method:

[0029] A guanylating agent, potassium carbonate and an aqueous solution of polyamino acid (the mass fraction of polyamino acid is 1-4 wt%) are mixed to obtain a reaction solution (in the reaction solution, the molar amount of the guanylating agent and potassium carbonate is equal); the degree of guanylation modification of the polyamino acid can be adjusted by adjusting the mass ratio (or molar ratio) of the guanylating agent and the polyamino acid; the reaction solution is reacted at 40-80° C. for 6-24 h in the presence of a protective atmosphere, and then precipitated and dried to obtain a guanylated derivative of the polyamino acid; the polyamino acid includes a linear homopolymer polyamino acid, a linear copolymer polyamino acid, a branched homopolymer polyamino acid or a branched copolymer polyamino acid. The guanylating agent includes 1H-pyrazole-1-carboxamidine hydrochloride, methoxyisourea (or its sulfate), 2-ethyl-2-thiourea sodium hydrobromide, etc.

[0030] Exemplarily, the method for preparing the acrylic polymer containing a quaternary ammonium group may adopt a reversible addition-fragmentation chain transfer polymerization (RAFT polymerization) method; specifically, the method comprises:

[0031] The acrylate monomer is mixed with an initiator, a chain transfer agent and a solvent to obtain a reaction solution (the mass of the initiator is 0.05-1.5 wt% of the total mass of the acrylate monomer, the mass of the chain transfer agent is 5-20 wt% of the total mass of the acrylate monomer, and the total mass concentration of the acrylate monomer, the initiator and the chain transfer agent in the reaction solution is 180-240 mg / mL); the reaction solution is reacted at 60-90° C. for 4-12 h in the presence of a protective atmosphere, and the acrylate polymer is obtained through sedimentation, centrifugation and drying; the acrylate monomer is an acrylate containing an amine group, an ammonium group, a pyridine group, a pyrrole group, a pyrazole group, an indole group residue, or an acrylate containing the above groups can be obtained by simple treatment after polymerization, including but not limited to any one of (meth) acrylate aminoethyl and its salt, (meth) acrylate-2-indoleethyl ester or a combination of at least two thereof. The initiator includes but is not limited to azo initiators and / or organic peroxide initiators; the azo initiator includes but is not limited to azobisisobutyronitrile (AIBN); the peroxide initiator includes but is not limited to dibenzoyl peroxide (BPO). The chain transfer agent includes but is not limited to dithioester derivatives, and the dithioester derivatives include but are not limited to isopropyl dithiobenzoate (CDB), 2-cyano-2-propyl dodecyl trithiocarbonate, 2-cyano-2-propyl benzodisulfide, 2-phenylpropanethiothiobenzoate, 2-(dodecyl trithiocarbonate)-2-methylpropionic acid, 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid, etc. The solvent in the RAFT polymerization includes but is not limited to dimethyl sulfoxide (DMSO).

[0032] Preferably, the amount of the water-soluble cationic polymer added is 0.2 to 26 parts, for example, 0.2 parts, 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts, 10 parts, 10.2 parts, 10.5 parts, 10.8 parts, 11 parts, 11.2 parts, 11.5 parts, 11.8 parts, 12 parts, 12.2 parts, 12.5 parts, 12.8 parts, 13 parts, 13.2 parts, 13.5 parts, 13.8 parts, 14 parts, 14.2 parts, 14.5 parts, 14.8 parts, 15 parts, 15.2 parts, 15.5 parts, 15.8 parts, 16 parts, 16.2 parts, 16.5 parts, 16.8 parts, 17 parts, 17.5 parts, 18 parts, 18.5 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 26 parts, and a range value composed of any two parts; preferably 2 to 18 parts, more preferably 7 to 15 parts.

[0033] In the present invention, when the amount of the water-soluble cationic polymer added is within a specific range, the residual amount of metal ions in the agglomerated particles is lower, the oxidation induction period is longer, the yellowing index is lower, and the prepared resin composition has excellent antibacterial and mildew-proof effects; when the amount of the water-soluble cationic polymer added is relatively small, the oxidation induction period of the agglomerated particles becomes shorter and the yellowing index increases; when the amount of the water-soluble cationic polymer added is relatively large, since the water-soluble cationic polymer can adsorb metal ions, when the amount added is too large, it cannot be completely washed away, and the residual amount will lead to an increase in the actual residual metal ion content, and will also induce yellowing, which will also lead to an increase in the yellowing index and a shortening of the oxidation induction period.

[0034] In the present invention, the addition amount of the vinyl polymer and the addition amount of the cationic polymer are both calculated based on solid mass, ie, the mass of the solvent is not included.

[0035] Preferably, the molecular structure of the vinyl polymer includes any one or a combination of at least two of structural units derived from conjugated dienes, structural units derived from styrene and its derivatives, structural units derived from acrylonitrile and its derivatives, or structural units derived from (meth) alkyl acrylates.

[0036] Preferably, the molecular structure of the vinyl polymer includes structural units derived from conjugated dienes and structural units derived from styrene and its derivatives, and also includes at least one of structural units derived from acrylonitrile and its derivatives and structural units derived from alkyl (meth)acrylates.

[0037] Preferably, the mass percentage of the structural units derived from conjugated dienes in the vinyl polymer is 50-80%, for example, it can be 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66%, 68%, 70%, 72%, 72.5%, 73%, 73.5%, 74%, 74.5%, 75%, 75.5%, 76%, 76.5%, 77%, 77.5%, 78%, 78.5%, 79%, 79.5%, 80%, and any two of the range values; preferably 55-78%, more preferably 60-75%; the mass percentage of the structural units derived from styrene and its derivatives is 5-36%, for example, it can be 5%, 5.5%, 6%, 6.5%, %, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%, 26%, 28%, 30%, 32%, 34%, 36% and ranges consisting of any two of them; the balance being structural units derived from acrylonitrile and its derivatives, and / or structural units derived from alkyl (meth)acrylates.

[0038] In the present invention, the mass percentage of each structural unit in the vinyl polymer is calculated based on the mass percentage of each monomer in the total monomers. For example, the mass percentage of the structural unit derived from conjugated diene in the vinyl polymer is 50-80%, which means that the conjugated diene monomer accounts for 50-80% of the total monomer mass.

[0039] In the present invention, the conjugated diene with carbon atoms ≥ 4 includes, but is not limited to, butadiene, isoprene, hexadiene, heptadiene, nonadiene, etc.; the styrene and its derivatives include, but are not limited to, any one of styrene, α-ethylstyrene, α-methylstyrene, p-methylstyrene, o-tert-butylstyrene, bromostyrene or chlorostyrene (such as trichlorostyrene) or a combination of at least two; acrylonitrile and its derivatives include, but are not limited to, acrylonitrile, methacrylonitrile, fumaronitrile, etc. The (meth) alkyl acrylate includes, but is not limited to, methyl methacrylate, methyl acrylate, butyl methacrylate, butyl acrylate, etc.

[0040] In the present invention, the vinyl polymer includes at least one of butadiene-styrene-acrylonitrile copolymer (ABS), butadiene-methyl methacrylate-styrene-acrylonitrile copolymer (MABS), butadiene-methyl methacrylate-styrene copolymer (MBS) or acrylonitrile-styrene-acrylate monomer copolymer (ASA).

[0041] Preferably, the oxidation induction period of the agglomerated particles in an air atmosphere at an isothermal temperature of 200° C. is ≥40 min, preferably ≥45 min, and more preferably ≥50 min.

[0042] Preferably, the a-value of the agglomerated particles measured by a Lab colorimeter is ≤8, preferably ≤6, and more preferably ≤4.

[0043] Preferably, the residual amount of metal salt in the agglomerated particles is ≤351 ppm, preferably ≤300 ppm, and more preferably ≤250 ppm.

[0044] In the present invention, the moisture content of the agglomerated particles is relatively low, and the moisture content is less than 0.25%.

[0045] In a second aspect, the present invention provides a method for preparing the agglomerated particles according to the first aspect, the preparation method comprising the following steps:

[0046] The agglomerated particles are obtained by mixing a latex of a vinyl polymer with a coagulant, subjecting the mixture to agglomeration and drying.

[0047] In the present invention, the latex of the vinyl polymer can be purchased from the market, or prepared by a conventional method. Exemplarily, the preparation method comprises the following steps:

[0048] (1) A solvent, an initiator, a chain transfer agent, an electrolyte, an emulsifier and a surfactant in an amount of 20% by weight are uniformly mixed at room temperature. In the presence of a protective atmosphere, a conjugated diene monomer is added thereto. The mixture is reacted at a temperature of 50 to 60°C and a rotation speed of 100 to 110 rpm for 6 to 12 h. The temperature is then raised to 65 to 75°C and the rotation speed is raised to 110 to 125 rpm for 8 to 16 h. The temperature is then further raised to 70 to 80°C and the rotation speed is raised to 135 to 135 rpm for 8 to 16 h. The remaining surfactant is then added thereto. The mixture is stirred for 20 to 40 min and then cooled to obtain a polyconjugated diene latex.

[0049] (2) The polyconjugated diene latex obtained in step (1), an initiator, a chain transfer agent, an emulsifier, a catalyst, a solvent and a grafting monomer (the grafting monomer includes at least two of styrene and its derivatives, acrylonitrile and its derivatives, and (meth) alkyl acrylate) are mixed, reacted at 50-60° C. for 1-6 hours, and then a surfactant is added thereto to continue the reaction for 0.5-3 hours to obtain the latex of the vinyl polymer.

[0050] In step (1) of the preparation method, the solvent includes water; based on 100 parts by mass of the conjugated diene monomer, the mass of the solvent is 80-120 parts; the initiator can be selected from commonly used initiators, including but not limited to one or more of potassium persulfate, ammonium persulfate or sodium persulfate; based on 100 parts by mass of the conjugated diene monomer, the mass of the initiator is 0.1-1 parts; the chain transfer agent can be selected from commonly used chain transfer agents, including but not limited to n-dodecyl mercaptan and / or tert-dodecyl mercaptan; based on 100 parts by mass of the conjugated diene monomer, the mass of the chain transfer agent is 0.2-1.2 parts; the electrolyte can be selected from commonly used electrolytes, including but not limited to sodium carbonate, carbon monoxide, etc. One or more of sodium bicarbonate, sodium hydroxide, potassium carbonate or potassium hydroxide; based on the mass of the conjugated diene monomer as 100 parts, the mass of the electrolyte is 0.1~1 part; the emulsifier can be selected from commonly used emulsifiers, including anionic emulsifiers; the anionic emulsifier includes but is not limited to one or more of disproportionated rosin acid soap, stearic acid soap, oleic acid soap, tallow fatty acid soap, lauric acid soap, alkylbenzene sulfonate, and sulfate ester salt; based on the mass of the conjugated diene monomer as 100 parts, the mass of the emulsifier is 0.1~1 part; the surfactant includes an acetylene alcohol surfactant, which can play the role of an emulsifier, and commonly used acetylene alcohol surfactants can be selected, including but not limited to one or more of methyl pentynol, 2,4,7,9-tetramethyl-5-decine-4,7,-diol, and ethyl octynol; based on the mass of the conjugated diene monomer as 100 parts, the total mass of the surfactant is 0.1~1 part.

[0051] In step (2) of the preparation method, the initiator, chain transfer agent, emulsifier, surfactant and solvent are selected from the same range of types as those in step (1); and the types of the components in step (1) and step (2) are the same or different; based on the mass of the dry basis of the polyconjugated diene latex as 100 parts, the mass of the initiator, chain transfer agent, emulsifier and surfactant is independently 0.1 to 1 part; the catalyst can be selected from commonly used catalysts according to the prior art, including but not limited to tetramethylethylenediamine and / or sodium formaldehyde sulfite; based on the mass of the dry basis of the polyconjugated diene latex as 100 parts, the mass of the catalyst is 0.2 to 2 parts, and the mass of the solvent is 100 to 140 parts.

[0052] Preferably, the coagulation is carried out under neutral conditions.

[0053] In the present invention, the neutral condition is adjusted by adding a pH adjuster, and the pH adjuster includes an organic acid and / or an inorganic acid; the functionality of the organic acid and / or the inorganic acid is 1 to 3, and is preferably sulfuric acid and / or acetic acid.

[0054] In the present invention, the mixing is carried out in a solvent, and the solvent includes water; the specific steps of the mixing include: using a pH regulator to adjust the latex of the vinyl polymer to neutrality; then pre-mixing the water-soluble cationic polymer with the solvent to obtain a coagulation liquid with a solid content of 4-10%; according to a formula in which the ratio of the added amount of the vinyl polymer (dry basis) to the water-soluble cationic polymer is 100:0.2-26 (both are calculated by solid weight), the coagulation liquid and the latex of the vinyl polymer are mixed at 50-95°C for standby use.

[0055] In the present invention, the solid content of the coagulation liquid is selected so that the cationic polymer can be fully dissolved, thereby obtaining a solution with a lower concentration and better fluidity.

[0056] Preferably, the condensation includes condensation through the steps of first heat preservation, temperature increase, second heat preservation and temperature reduction.

[0057] Preferably, the temperature of the first insulation is 70-80°C, for example, 70°C, 72°C, 74°C, 75°C, 76°C, 78°C, 80°C, etc.; the time is 1-10 min, for example, 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7min, 8 min, 9 min, 10 min, etc.

[0058] Preferably, the heating rate of the heating is 3-7°C / min, for example, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, etc.

[0059] Preferably, the temperature of the second insulation is 90-100°C, for example, it can be 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C, 100°C, etc.; the time is 5-15 min, for example, it can be 5 min, 6 min, 7min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, etc.

[0060] Preferably, the cooling rate is 0.5-4°C / min, for example, 0.5°C / min, 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, etc., down to room temperature.

[0061] In the present invention, before drying, the slurry obtained by coagulation is subjected to solid-liquid separation; the solid-liquid separation can be carried out by filtering, centrifugal dehydration or spray drying. In order to improve the whiteness of the coagulated rubber powder, the dehydrated rubber powder can be washed. The drying step can be hot air drying on a fluidized bed at a drying temperature of 50-70°C; or it can be extrusion dehydration on a wet extruder.

[0062] In a third aspect, the present invention provides a resin composition, which comprises, in parts by weight, 65 to 95 parts of resin (for example, 65, 66, 68, 70, 72, 74, 76, 78, 80, 82, 84, 86, 88, 90, 92, 94 parts, or a range consisting of any two of them) and 5 to 35 parts of the agglomerated particles described in the first aspect (for example, 5, 6, 8, 10, 12, 14, 16, 18, 20, 22, 24, 26, 28, 30, 32, 34 parts, or a range consisting of any two of them).

[0063] Preferably, the resin includes at least one of styrene-acrylonitrile copolymer, polymethyl methacrylate, methyl methacrylate-styrene-acrylonitrile terpolymer, polystyrene, polyvinyl chloride, polycarbonate, polypropylene, polyphenylene ether, polyester and polyamide.

[0064] Preferably, the antibacterial rate of the resin composition is ≥90%, preferably ≥95%, more preferably ≥99%, and particularly preferably ≥99.9%; the mildew resistance level is 0-1.

[0065] In the present invention, the agglomerated particles can also be used as a good impact modifier and can be mixed and kneaded with other resin materials to form a resin composition. The impact strength of the resin composition can be improved as the content of the agglomerated particles increases.

[0066] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0067] Compared with the prior art, the present invention has the following beneficial effects:

[0068] The condensed particles provided by the present invention use a water-soluble cationic polymer having a nitrogen-containing functional group as a coagulant, and the number average molecular weight of the water-soluble cationic polymer is within a specific range. The obtained condensed particles have low metal ion residues, a long oxidation induction period and a low yellowing index. The resin composition including the condensed particles also has excellent heat-oxidative aging resistance, as well as good antibacterial and mildew-proof effects and impact resistance. DETAILED DESCRIPTION

[0069] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0070] In the present invention, the test method for the solubility of the materials used is carried out with reference to the method specified in GB / T 21845-2008 "Test for Water Solubility of Chemicals".

[0071] In the present invention, the test method for the surface potential of the materials used is carried out with reference to the method specified in GB / Z 42353-2023 "Zeta Potential Determination Operation Guide".

[0072] In the present invention, the test method of the weight average molecular weight or number average molecular weight of the materials used refers to GB / T31816-2015 "Water treatment agent polymer molecular weight and its distribution determination gel chromatography method", and the test is performed using Waters model ACQUITY ultra-high performance polymer chromatography (APC) gel filtration chromatograph.

[0073] In the present invention, the water content of the latex agglomerated particles is determined by referring to the method specified in GB / T 2914-2008 "Determination of volatile matter (including water) in plastic vinyl chloride homopolymer and copolymer resins". The water content of the agglomerated particles provided by the present invention is 0.2%.

[0074] In the present invention, the pH value is tested using the JJ-119-84 laboratory pH (acidity) meter verification procedure.

[0075] The materials used in the present invention can be purchased from the market or prepared by conventional methods. Unless otherwise specified, the materials used in the present invention are as follows:

[0076] Preparation Example 1: Preparation of latex of vinyl polymer (A)

[0077] Latex of vinyl polymer A1

[0078] Calculated by mass percentage, the molecular structure of the vinyl polymer A1 includes 73% of structural units derived from butadiene, 18% of structural units derived from styrene and 9% of structural units derived from acrylonitrile.

[0079] The preparation method of the latex of the vinyl polymer A1 comprises:

[0080] Step S1: 100 parts of water, 0.4 parts of ammonium persulfate, 0.6 parts of n-dodecyl mercaptan, 0.4 parts of sodium carbonate, 0.4 parts of potassium stearate and 0.08 parts of ethyl octynol are added to a reactor, and stirred at room temperature until completely dissolved and mixed; nitrogen is introduced into the reactor to replace the air so that the oxygen content is less than 10 ppm, and then 100 parts of butadiene monomer are added; the reactor is heated to 55° C. and reacted at a constant temperature for 9 hours as a first stage polymerization reaction, and the stirring speed is controlled to 105 rpm; after the first stage polymerization reaction is completed, the system is heated to 70° C. and reacted at a constant temperature for 12 hours as a second stage polymerization reaction, and the stirring speed is controlled to 120 rpm; after the second stage polymerization reaction is completed, the system is heated to 75° C. and reacted at a constant temperature for 12 hours as a third stage reaction, and the stirring speed is controlled to 130 rpm, and 0.32 parts of ethyl octynol are added at the end of the polymerization reaction, and the temperature is lowered after stirring for half an hour to obtain polybutadiene latex.

[0081] Step S2: Heat the polybutadiene latex in step S1 to 55°C, add 0.4 parts of ammonium persulfate, 0.6 parts of n-dodecyl mercaptan, 0.4 parts of potassium stearate, 1 part of tetramethylethylenediamine and 120 parts of water, based on 100 parts of the dry mass of the polybutadiene latex, and add the formulated amount of acrylonitrile monomer and the formulated amount of styrene-based monomer, and continue to drop for 2 hours. After the dropwise addition is completed, continue to react for 3 hours, then add 0.4 parts of ethyl octynol, continue to react at 55°C for 2 hours, and then cool to room temperature to obtain the latex of the vinyl polymer A1.

[0082] Latex of vinyl polymer A2~A7

[0083] The preparation method of the latex of vinyl polymers A2 to A7 is the same as that of vinyl polymer A1, the only difference is that the types and masses of the structural units of the vinyl polymers are different, that is, the types and ratios of monomers are different (the total amount of monomers is the same), calculated in terms of mass percentage (the total amount of monomers is 100%), and the specific formula is shown in Table 1; wherein, “ / ” indicates that the component is not included in the formula.

[0084] Table 1

[0085]

[0086] Preparation Example 2: Preparation of water-soluble cationic polymer (B)

[0087] Table 2

[0088]

[0089] Among them, the preparation method of B1 includes: adding 91.32 g of lysine hydrochloride and 28.05 g of KOH solution (20wt%) into a 500 mL round-bottom flask, connecting a water separation device, pumping nitrogen three times, each time for more than 10 minutes, and finally maintaining a nitrogen atmosphere. After stirring and heating the reaction at 250°C for 30 minutes, the heating is stopped, and the obtained product is dissolved in methanol and precipitated in ether to obtain branched polylysine B1.

[0090] B2: purchased from McLean, product number P832584.

[0091] The preparation method of B3 comprises: dissolving 331 mg of 2-aminoethylmethacrylate (AEMA), 229 mg of 2-(1H-indol-3-yl)ethyl methacrylate (IEMA), 7 mg of azobisisobutyronitrile (AIBN) and 81 mg of chain transfer agent 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid in 3 mL of dimethyl sulfoxide (DMSO), and heating the mixture under high vacuum (10 °C). -3 Torr) for three freeze-pump-thaw cycles, then heated to 70°C for 8 h. The obtained product was purified by three methanol-ether precipitations, centrifuged three times, and dried to obtain a copolymer of aminoethyl methacrylate and 2-indoleethyl methacrylate, which belongs to the acrylic acid ester copolymer containing quaternary ammonium groups.

[0092] The preparation method of B41 includes: adding 91.32 g of lysine hydrochloride and 28.05 g of KOH solution (20 wt%) into a 500 mL round-bottom flask, connecting a water separator, pumping nitrogen three times, each time for more than 10 minutes, and finally maintaining a nitrogen atmosphere. After stirring and heating at 250° C. for 40 min, heating is stopped, and the obtained product is dissolved with methanol and precipitated into ether to obtain branched polylysine; then 1.46 g of 1H-pyrazole-1-carboxamidine hydrochloride and 1.38 g of potassium carbonate are added to 80 g of an aqueous solution containing 2.5 wt% of branched polylysine; after pumping nitrogen three times, the mixed solution is heated at 60° C. for 12 h, then precipitated with ether, and vacuum dried to obtain guanidinium branched polylysine B41, which is a guanidinium derivative of branched polyamino acids.

[0093] B42: The only difference between it and B41 is that, in the preparation method, the reaction is stirred and heated at 250° C. for 60 min, and the amounts of other raw materials and step parameters are the same as those of B41.

[0094] B43: The only difference between it and B41 is that, in the preparation method, the reaction is stirred and heated at 250° C. for 25 min, and the amounts of other raw materials and step parameters are the same as those of B41.

[0095] B44: The only difference between it and B41 is that, in the preparation method, the reaction is stirred and heated at 250° C. for 15 min, and the amounts of other raw materials and step parameters are the same as those of B41.

[0096] B45: The only difference between it and B41 is that, in the preparation method, the reaction is stirred and heated at 250° C. for 90 min, and the amounts of other raw materials and step parameters are the same as those of B41.

[0097] B46: The only difference between it and B41 is that, in the preparation method, the stirring heating reaction is carried out at 250° C. for 150 min, and the amounts of other raw materials and step parameters are the same as those of B41.

[0098] Example 1

[0099] The present embodiment provides a condensed particle, which includes a vinyl polymer A1 and a water-soluble cationic polymer B1. Based on 100 parts by weight of the vinyl polymer A1, the amount of the water-soluble cationic polymer B1 added is 10.5 parts by weight.

[0100] This embodiment provides a method for preparing agglomerated particles, comprising the following steps:

[0101] A water-soluble cationic polymer B1 is mixed with water to obtain a water-soluble cationic polymer aqueous solution with a solid content of 4.3%; concentrated sulfuric acid is used to adjust the latex of the vinyl polymer A1 to neutrality, and then the latex of the vinyl polymer A1 is added to the cationic polymer aqueous solution at 75°C in 4 times according to the formula, and the amount added each time is 25% of the total amount of the latex; the obtained mixture is then maintained at 75°C for 5 minutes, the temperature is increased to 95°C at a heating rate of 5°C / min and maintained for 10 minutes, and then the temperature is reduced to room temperature at a cooling rate of 2°C / min to obtain a coagulation slurry; the coagulation slurry is dehydrated by a centrifugal dehydrator, and then dried on a boiling bed at 60°C to obtain the coagulated particles.

[0102] Examples 2 to 19, Comparative Examples 1 to 3

[0103] Examples 2 to 19 and Comparative Examples 1 to 3 respectively provide a kind of condensed particles, which differ from Example 1 only in that the types of vinyl polymers, types of coagulants and their contents are different. The specific formulas are shown in Tables 2, 3 and 4, where " / " indicates that the component is not included in the formula. In particular, the water-soluble cationic polymer B46 used in Comparative Example 1 has poor water solubility, and a completely dissolved aqueous solution cannot be obtained under the same formula and conditions. B46 is dispersed in the condensed particles in the form of solid / semi-solid. Comparative Example 2 uses glacial acetic acid as the coagulant, which cannot completely demulsify. During solid-liquid separation, the liquid part still contains a large amount of latex, and the aqueous phase is milky white. When used, only the part that has been condensed and demulsified is taken, while the other examples and comparative examples completely demulsify during the condensation process, and the aqueous layer is a clear and transparent yellow to light yellow solution during solid-liquid separation.

[0104] Table 3

[0105]

[0106] Table 4

[0107]

[0108] Table 5

[0109]

[0110] Application Examples

[0111] This application example provides a resin composition, which includes 20 parts by weight of agglomerated particles and 80 parts of SAN resin (resin brand KFA-130, Liaoning Jinfa); the agglomerated particles are the agglomerated particles provided in Examples 1 to 19 and Comparative Examples 1 to 3.

[0112] Performance Testing

[0113] (1) Metal residue

[0114] The agglomerated particles were digested and the residual metal ion content in the agglomerated particles was determined by inductively coupled plasma atomic emission spectrometry (ICP) with reference to HG / T 3944-2007 “ICP method for determination of metal ion content in polyvinyl chloride resin”.

[0115] (2) Oxidation induction period

[0116] The oxidation induction period of the agglomerated particles was tested with reference to the national standard GBT 19466.6-2009 "Plastics Differential Scanning Calorimetry (DSC) Part 6: Oxidation Induction Time (Isothermal OIT) and Oxidation Induction Temperature (Dynamic OIT)". Specifically, the OIT was tested under isothermal conditions of 200°C in an air atmosphere.

[0117] (3) Heat aging and yellowing resistance

[0118] The dried agglomerated particles were placed into multiple aluminum foil watch glasses and placed in a constant temperature oven at 180°C. After 24 hours of constant temperature, the samples were taken out and the b value of the agglomerated particles was tested using a Lab colorimeter. The larger the b value, the worse the heat aging yellowing performance.

[0119] (4) Antibacterial and anti-mildew properties

[0120] The resin composition including the agglomerated particles is mixed by a twin-screw extruder, and is pressed into a sheet on a flat vulcanizer at an upper and lower plate temperature of 200° C. to prepare a sheet of (50±2) mm×(50±2) mm with a thickness not exceeding 10 mm, and the antibacterial and anti-mildew properties of the resin composition are tested;

[0121] The antibacterial performance is tested with reference to the national standard GB T 31402-2015 "Test Method for Antibacterial Performance of Plastic Surfaces for Antibacterial Performance of Materials". Specifically, the antibacterial test adopts the film method, and the operation steps are as follows: After the sample to be tested is disinfected, a bacterial suspension is inoculated on its surface and covered with a polyethylene film to form a uniform liquid film between the sample and the film. After culturing under certain conditions, it is eluted and diluted into an appropriate concentration gradient. A certain volume is applied to the culture medium for re-culturing and the number of viable bacteria is determined to calculate the antibacterial rate. The antibacterial rate calculation formula is: Antibacterial rate % = (the number of bacteria of a pure resin sample after 24 hours - the number of bacteria of the corresponding embodiment or comparative sample after 24 hours) / the number of bacteria of a pure resin sample after 24 hours * 100%. Detection bacteria: Escherichia coli ATCC 25922.

[0122] The anti-mildew performance is tested with reference to the national standard GB21551.2-2010 "Special requirements for antibacterial materials with antibacterial, sterilization and purification functions for household and similar electrical appliances"; among them, 0 represents the highest anti-mildew level, and 3 represents the lowest anti-mildew level.

[0123] (5) Impact resistance: The resin composition including the agglomerated particles is mixed by a twin-screw extruder, and the resin composition is injection molded into a standard specimen with a notch according to the requirements of "GB / T 1843-2008 Determination of Izod impact strength of plastics" and its Izod notch impact strength is tested.

[0124] The specific test results are shown in Table 6.

[0125] Table 6

[0126]

[0127] In addition, taking Example 1 as an example, the Izod notched impact strength of the resin composition including the agglomerated particles provided in Example 1 and the SAN resin (resin grade KFA-130, Liaoning Jinfa) without the agglomerated particles (control group) was tested.

[0128] The test results show that the notched Izod impact strength of the resin composition including the agglomerated particles provided in Example 1 is 32.2 kJ / m 2 ; The notched cantilever beam impact strength of the control group is 9.1 kJ / m 2 It can be seen that the agglomerated particles provided by the present invention can improve the impact strength of the resin, which proves that the agglomerated particles provided by the present invention can be used as an impact modifier.

[0129] In summary, the condensed particles provided by the present invention use a water-soluble cationic polymer with a nitrogen-containing functional group as a coagulant, and the number average molecular weight of the water-soluble cationic polymer is within a specific range, and the obtained condensed particles have low metal residue, a long oxidation induction period and a low yellowing index; the oxidation induction period of the condensed particles in an air atmosphere and isothermal conditions of 200°C is ≥40 min, and after continuous baking at 180°C in an oven for 24 hours, the condensed particles obtained by the present invention are whiter in color, have a b value of less than 7, and have a metal residue of less than 351 ppm compared to the comparative example; the antibacterial rate of the resin composition including the condensed particles reaches more than 90%, and the mildew resistance level is 0~1.

[0130] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A condensed particle, characterized in that: The condensed particles include a vinyl polymer and a condensing agent; The coagulant includes a water-soluble cationic polymer having nitrogen-containing functional groups; The amount of the water-soluble cationic polymer added is 0.2 to 26 parts based on 100 parts of the vinyl polymer; The number average molecular weight of the water-soluble cationic polymer is 1000-12000 g / mol; At 25°C and pH 5-9, the surface potential of the water-soluble cationic polymer is 12-75 mV; The nitrogen-containing functional group includes at least one of an amide group, an amine group, an ammonium group, a guanidine group or a nitrogen-containing aromatic group; The molecular structure of the vinyl polymer includes any one or a combination of at least two of structural units derived from conjugated dienes, structural units derived from styrene and its derivatives, structural units derived from acrylonitrile and its derivatives, or structural units derived from (meth) alkyl acrylate.

2. The agglomerated particles according to claim 1, characterized in that At room temperature, the solubility of the water-soluble cationic polymer is ≥10 g / L.

3. The agglomerated particles according to claim 1, characterized in that The water-soluble cationic polymer includes at least one of chitosan, polyamino acids and derivatives thereof, polyhexamethylene biguanide and salts thereof, acrylic acid ester polymers containing quaternary ammonium groups, or polycarbonate polymers containing quaternary ammonium groups.

4. The agglomerated particles according to claim 3, characterized in that The polyamino acid and its derivatives include at least one of polyamino acid, quaternized derivatives of polyamino acid, guanidated derivatives of polyamino acid or quaternized and guanidated derivatives of polyamino acid.

5. The agglomerated particles according to claim 1, characterized in that The molecular structure of the vinyl polymer includes structural units derived from conjugated dienes and structural units derived from styrene and its derivatives, and also includes at least one of structural units derived from acrylonitrile and its derivatives and structural units derived from alkyl (meth)acrylates.

6. The agglomerated particles according to claim 5, characterized in that In the vinyl polymer, the mass percentage of the structural units derived from conjugated dienes is 50-80%, the mass percentage of the structural units derived from styrene and its derivatives is 5-36%, and the balance is structural units derived from acrylonitrile and its derivatives, and / or structural units derived from alkyl (meth)acrylates.

7. The agglomerated particles according to claim 1, characterized in that The oxidation induction period of the agglomerated particles in an air atmosphere at an isothermal temperature of 200° C. is ≥ 40 min; The ab value of the agglomerated particles tested by a Lab colorimeter is ≤8; The residual amount of metal salt in the agglomerated particles is ≤351 ppm.

8. A method for preparing agglomerated particles according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: The agglomerated particles are obtained by mixing a latex of a vinyl polymer with a coagulant, subjecting the mixture to agglomeration and drying.

9. The preparation method according to claim 8, characterized in that: The coagulation is carried out under neutral conditions; The condensation includes condensation through the steps of first heat preservation, temperature increase, second heat preservation and temperature reduction; The first insulation temperature is 70-80°C and the time is 1-10 min; The heating rate of the heating is 3-7°C / min; The second insulation temperature is 90-100°C and the time is 5-15 min; The cooling rate is 0.5-4°C / min, down to room temperature.

10. A resin composition, characterized in that In parts by weight, the resin composition comprises 65 to 95 parts of resin and 5 to 35 parts of the agglomerated particles according to any one of claims 1 to 7.

11. The resin composition according to claim 10, characterized in that The resin includes at least one of styrene-acrylonitrile copolymer, polymethyl methacrylate, methyl methacrylate-styrene-acrylonitrile terpolymer, polystyrene, polyvinyl chloride, polycarbonate, polypropylene, polyphenylene ether, polyester and polyamide; The antibacterial rate of the resin composition is ≥90%, and the mildew resistance level is 0-1.

Citation Information

Patent Citations

  • Polymer latex agglomerated particles and preparation method thereof

    CN114085338A